A Quantified Description of the Coupling between the Reaching Direction and Elbow Axis Direction - M. M. Stanišić; C. M. Goehler; M. Tomšič (Applied Bionics and Biomechanics)
The human body continues to be an inspiration for the work of a myriad of different fields, both scientific and mathematic. In particular, robotics draws upon the motions and relationships of different human systems in order to reproduce similar mobility while performing different tasks. The human shoulder–arm–elbow complex has been one of the most difficult to exactly replicate. This paper examines the relationship between the motion of the shoulder while positioning the center of the wrist during voluntary arm movements and the resulting orientation of the arm, in particular the direction of the axis passing through the elbow joint. Experimental data is presented that was used to quantify this coupling between the reaching direction of the arm and the elbow axis direction. The results from this paper are two surface-fit equations that can be used to determine the elbow axis direction when given the location of the wrist center. These results are useful when considering the design and control of shoulder–arm–elbow complex models.